Find the inverse function of f(x)=14 + root(3)(x).
y = 14 + root(3)(x) x = 14 + root(3)(x)
and then I would cube both sides?
did you mean to replace that one x with y?
Oh, yes. I have to find f^-1(x)
right isolate the cuberoot(y) part first by subtracting that other number on both sides then you can talk about cubing both sides
x-14 = root(3)(y)
(x-14)^3 = y
f^-1(x) = (x-14)^3
that is right that is the inverse function of f
thanks for the help
i didn't do anything you did it all by yourself congrats! :)